Antimicrobial susceptibility patterns and MICs among non‐photochromogenic rapidly growingMycobacteroidesandMycolicibacteriumspecies. Issue 9 (September 2019) - Yoshida, Shiomi; Tsuyuguchi, Kazunari; Chikamatsu, Kinuyo; Aono, Akio; Takaki, Akiko; Mitarai, Satoshi; Kobayashi, Takehiko; Inoue, Yoshikazu; Suzuki, Katsuhiro
N/A: Introduction. : Non‐photochromogenic rapidly growing mycobacteria (NPRGM) that branch distinctly from Mycobacteroides (Myco) and Mycolicibacterium (Mycolici) are increasingly observed clinically and present a complicated treatment challenge; thus, appropriate in vitro susceptibility testing is required. Methodology. : We evaluated the MICs of nine antimicrobials used in the treatment of infections of 25 NPRGM type strains. The relation of inducible macrolide resistance with functional erythromycin ribosomal methylase ( erm ) genes was also investigated. Results. : The initial clarithromycin MIC reading at 3 days showed resistance in four of the Mycolici strains. In contrast, the presence of erm genes among Mycolici species differed from previous findings. Both Myco and Mycolici species were highly susceptible to amikacin and linezolid. Myco species were resistant to fluoroquinolones, while Mycolici species were susceptible. Meropenem showed low activity against Myco species, but high activity against Mycolici species. Conclusion. : NPRGM clade‐specific susceptibility patterns suggest an urgent need to establish distinct breakpoints for Myco and Mycolici species.